PERBANDINGAN TINGKAT PARTISIPASI PEMILIH PEMULA PADA PEMILIHAN WALIKOTA PALEMBANG TAHUN 2008 DAN TAHUN 2013 - Yan Sinatra; Isabella Isabella (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The focus of this study is the comparison of the level of participation of voters on Election Mayor of Palembang in 2008 and in 2013 as well as the factors that influence the level of participation of the voters. While the purpose of this study was to determine and analyze comparative novice voter turnout on Election Mayor of Palembang in 2008 and in 2013 as well as the factors that influence the level of participation of the voters. Overall voter turnout on Election Mayor of Palembang in 2008 as many as 682,445 voters, while at the Election Mayor of Palembang in 2013, overall voter turnout as much as 757 797 voters. Based on these data, it turns voter turnout in the city of Palembang is not too high only around 67% in 2008 while in the year 2013 down to 63%. While the voter turnout for the beginner, the Year 2008 of the number of voters as much as 156 493 people, which gives the percentage voting rights of 70% or 109 545 souls who turn out to vote. Participation rate for the beginner in 2013, the number of voters as many as 283 372 people, which gave voting rights percentage drops to 65% or as much as 184 192 souls who turn out to vote.Key Words: Participation, Level of Participation, Election Mayor of Palembang